Determination of Iron in Iron Tablets by Spectrophotometry and Atomic Absorption Spectroscopy - Rajbhandari, Armila (International Journal of Pharmaceutical & Biological Archive, 2013)
Determination of Iron in Iron Tablets by Spectrophotometry and Atomic Absorption Spectroscopy